Systematic Review of the Patterns of Orofacial Injuries in Physically Abused Children and Adolescents. (January 2021) - Sarkar, Reena; Ozanne-Smith, Joan; Bassed, Richard
Objective: To examine the evidence base for patterns of oro-facial injuries in physical abuse cases of children and adolescents aged 0-17 years. Data sources: Systematic searches of Ovid Medline, Ovid Embase, Cochrane Central and grey literature, dating from the oldest entry to August 2017. Review methods: Search criteria included English language peer reviewed articles and theses on physical abuse cases affecting the age group of 0-17 years. Exclusion criteria were: Case reports and <10 case series; studies involving bite mark injuries elsewhere on the body, sexual, ritualistic or emotional abuse and neglect, exposure to domestic violence; reviews; book chapters and conference proceedings. The following data was extracted: quality and design of study, oro-facial manifestations, new/old injuries, fatalities, coexistent injuries, co-morbidities and radiologic investigations. Each study was subjected to two independent reviews and a third, if reviewers disagreed. Results: The authors identified 51 articles, 26 of which satisfied the inclusion criteria. The oro-facial signs were superficial injuries of face, ears, neck, lips and oral mucosa, burns, torn fraenii and fractured teeth and jaws. A minority of studies stood out due to their well-developed design; expert opinion inclusion; new/old/occult injury investigations and facial bruising/ intraoral injuries as sentinel markers. Overall, the review demonstrated weak study quality and representativeness as well as lacunae in uniform reporting. Conclusions: The available literature does not endorse any pathognomonic signature patterns of child physical abuse to the exposed oro-facial region.